The man who loved flies: a biographical profile of Nelson Papavero - Klassa, Bruna; Santos, Charles Morphy D. (Zootaxa, 2014)
Nelson Papavero is one of the major Brazilian zoologists. His contribution to the field began in the second half of the twentieth century, when he started publishing in the areas of entomology, systematics, biogeography, and history of science, while working at graduate courses and training teachers and students. Papavero was one of the earliest Brazilian advocates of Hennig’s phylogenetic systematics. In his entomological work, his first widely recognised works were the Catalogue of South American Diptera and his essays on the history of Neotropical Dipterology. Papavero’s greatest contribution however, is in his Special Courses on Zoological Systematics, as well as his numerous administrative positions during his academic career. All these were fundamental to the development of zoology and comparative biology in Brazil and other Latin American countries. Here we present a biography of Nelson Papavero, along with several personal anecdotes, and his role in the development of Brazilian biological systematics over the last 50 years.